The Efficacy of Artwork as a Self-Care Technique to Address Distress in an International Student Studying in Australia - Yin Ki Lai; Katrina Andrews (Psychotherapy and Counselling Journal of Australia)
This paper reports on an art-based autoethnography study aimed at helping the author, an international student, reflect on her personal distress during tertiary study in Australia. Over an 8-week period, the author engaged in meditation and art-making activities to articulate and reflect upon her experiences and emotions. Distress levels were recorded using the Visual Analogue Scale before and after each session of art making and reflection. The findings indicate a reduction in the author’s distress levels following engagement in art making and reflection. Furthermore, the process revealed the importance of maintaining a positive mindset and cultivating self-love, which contributed to the author’s reduced distress levels. In conclusion, this study reveals that engaging in art making effectively alleviated distress for the author during her time as an international student in Australia.